2015
DOI: 10.1002/jwmg.907
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of wood duck recruitment from nest boxes in Mississippi and Alabama

Abstract: Since the early 20th century, wildlife managers have deployed artificial nesting structures for wood ducks (Aix sponsa) to increase availability of nest sites and local reproduction of the species. However, knowledge is lacking of the effects of nest structure size (i.e., large vs. small; Stephens et al. 1998) and reproductive data (e.g., clutch size, hatch date, duckling survival) on recruitment of wood ducks. We used stochastic simulation analyses to predict recruitment of wood ducks into late summer by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Installing nest boxes in inconspicuous locations, or at lower densities, can reduce the probability of nests being parasitized (Semel and Sherman ). We concur with other authors and suggest this relationship deserves further attention (Semel and Sherman , Roy Nielsen et al , Hafen and Koons ), particularly as it relates to nest box placement and management and to the identification of an optimal brood size (Heusmann ; Rohwer and Heusmann ; Davis et al , ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Installing nest boxes in inconspicuous locations, or at lower densities, can reduce the probability of nests being parasitized (Semel and Sherman ). We concur with other authors and suggest this relationship deserves further attention (Semel and Sherman , Roy Nielsen et al , Hafen and Koons ), particularly as it relates to nest box placement and management and to the identification of an optimal brood size (Heusmann ; Rohwer and Heusmann ; Davis et al , ).…”
Section: Discussionsupporting
confidence: 90%
“…Patterns in habitat selection were consistent with previous research that identified use of woody or dense vegetative cover (McGilvrey , Sousa and Farmer , Smith and Flake , Granfors and Flake , Davis et al ). Brood and duckling survival may limit recruitment at our northern study area and additional data collection is required to support life‐cycle analysis (Coluccy et al , Davis et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Managers can potentially use our results to inform conservation action, reduce losses of eggs, nestlings and adults to predation, and indirectly promote nest site fidelity by increasing the likelihood of successful nesting. Furthermore, our results support growing evidence that the type of nest box array used in avian research is not trivial and may introduce an unexamined source of variation in reproduction studies (Lambrechts et al , Møller et al , Davis et al , Bueno‐Enciso et al , Demeyrier et al ).…”
Section: Management Implicationssupporting
confidence: 85%